The Relationship Between Organizational Stress and Job Satisfaction Among Pre-University Teaching Staff - Sandu, Mihaela Luminița; Rus, Mihaela; Iliuță (Pârlica), Elena (Technium Social Sciences Journal, 2023)
In this era of constant change and highly competitive environments, school efficiency is considered a key factor in successful organization. To ensure the success of educational systems and policies that are seamlessly implemented, schools require motivated and satisfied teachers who feel secure in their workplace and are capable of meeting high standards in their tasks. On the other hand, the continuous monitoring of teachers in the implementation of new curriculum policies, teaching and learning evaluation can diminish motivation, effectiveness, and job satisfaction. Furthermore, the academic literature has recognized teaching as a profession with high levels of stress. This study aimed to investigate the relationship between stress and professional satisfaction among pre-university teachers. The motivation for choosing this topic is primarily grounded in the idea that we all desire to build and maintain a mentally and emotionally balanced, healthy environment that enriches our quality of life and provides a conducive framework for personal growth and development. It also helps us become more aware of and optimize our relationships with the environment we live in, with others, and even with ourselves.